National Mortality Followback Survey, 1966-1968 ([Verlag nicht ermittelbar], 1986)
This survey was designed primarily to obtain information on the smoking habits of decedents by examining death certificates and questionnaires mailed to death record informants. Smoking variables in this data collection include number of cigarettes smoked when the decedent smoked most, number smoked the year before death, number smoked three years before death, and cigar and pipe smoking occurrence three years before death. Demographic variables include marital status, family type, number of children, living arrangements, size of family, birth and death of the decedent, family income and family debt, and cause of death.